Overview of the Evolution and Trends of the QuEChERS Sample Preparation Procedure - Veiga-del-Baño, José M.; Andreo-Martínez, Pedro; Pérez-Lucas, Gabriel; Navarro, Simón (Reviews of environmental contamination and toxicology, 2024)
The quick, easy, cheap, effective, rugged, and safe (QuEChERS) method is a sample preparation technique originally used in analytical chemistry for the extraction and purification of pesticide residues in food. In recent years, the approach has evolved beyond its original scope to include environmentally relevant analytes other than pesticides and matrices other than food. The main objective of this paper is to provide a chronological overview of bibliometrics and to present the development of QuEChERS applications from publishing the method in 2003 to present using the tools BibExcel, VOSviewer, and Bibliometrix. A bibliometric analysis was carried out using the Science Citation Index Expanded database (WoS©) to analyze the scientific literature published in the field over the last 20 years and to identify limitations and future research directions. Yearly production of scientific publications increased steadily, and Price's index (50.3%) showed that QuEChERS method research is still relevant after 20 years. China and the USA were the most productive and collaborative countries in the field, and all the documents (4789) were published in 56 different subject categories of WoS©, which implies that QuEChERS method research is multidisciplinary in nature. This is the first bibliometric review of the QuEChERS method, where trend topics in the keywords show the evolution of the QuEChERS method into other fields complementary to pesticide analysis as a risk in food safety. Graphical abstract